2021
DOI: 10.1126/science.abg0399
|View full text |Cite
|
Sign up to set email alerts
|

Electric field–tunable superconductivity in alternating-twist magic-angle trilayer graphene

Abstract: Engineering moiré superlattices by twisting layers in van der Waals (vdW) heterostructures has uncovered a wide array of quantum phenomena. Here, we construct a vdW heterostructure consisting of three graphene layers stacked with alternating twist angles ±θ. At the average twist angle θ ~ 1.56°, a theoretically predicted magic angle for the formation of flat electron bands, we observed displacement field tunable superconductivity with a maximum critical temperature of 2.1 K. By tuning the doping level and disp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
307
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 375 publications
(343 citation statements)
references
References 52 publications
(53 reference statements)
31
307
2
3
Order By: Relevance
“…In 2019, Ashvin Vishwanath of Harvard university predicted that multilayer graphene with alternating twist angles would also exhibit superconductivity. This was very recently confirmed, and it was found that at an average angle of ±1.56°, twisted trilayer graphene exhibited extraordinary superconductive properties and considering its low charge density, it had the strongest electron pairing ever observed [14]. tTLG was noted As superior to bilayer graphene because it was superconductive at a higher temperature and had better tunability in terms of its electronic structure and superconducting characteristics than bilayer graphene [15].…”
Section: Introductionmentioning
confidence: 74%
“…In 2019, Ashvin Vishwanath of Harvard university predicted that multilayer graphene with alternating twist angles would also exhibit superconductivity. This was very recently confirmed, and it was found that at an average angle of ±1.56°, twisted trilayer graphene exhibited extraordinary superconductive properties and considering its low charge density, it had the strongest electron pairing ever observed [14]. tTLG was noted As superior to bilayer graphene because it was superconductive at a higher temperature and had better tunability in terms of its electronic structure and superconducting characteristics than bilayer graphene [15].…”
Section: Introductionmentioning
confidence: 74%
“…Yet, superconductivity has been found in a growing number of materials in such strong-coupling regime. Two famous examples are (i) strontium titanate, the most dilute bulk superconductor with Fermi energy as small as 1 meV (6), and (ii) magic-angle graphene with a record-low density n 2D ∼ 10 11 cm −2 and a very small bandwidth of ∼10 meV (7)(8)(9)(10). The ratio of superconducting transition temperature T c and Fermi temperature E F /k B far exceeds typical values, reaching as high as 0.01 in strontium titanate (6) and 0.1 in magic-angle graphene (8).…”
Section: Introductionmentioning
confidence: 99%
“…As paradigmatic examples, twisted graphene bilayers have realized unconventional superconductivity [3], topological networks [6], strange metals [20], and Chern insulators [9]. More complex twisted graphene multilayers, such as twisted bi-bilayers [7,10] and trilayers [21][22][23], have provided additional platforms to realize similar physics as twisted graphene bilayers. The possibility of tuning several twist angles in multilayer graphene [24][25][26][27][28] suggests that these systems may realize correlated states of matter beyond the ones already observed in twisted bilayers.…”
mentioning
confidence: 99%